CHANGES OF THE LEVEL OF PHYSICAL FITNESS OF BOXING TEAMS FROM HIGHER MILITARY EDUCATIONAL INSTITUTIONS IN THE PRE-COMPETITIVE PERIOD (Physical Culture and Sport: Scientific Perspective, 2024)
In today's sports of high achievements, additional influencing factors that contribute to increasing the level of sportsmanship amongst men and women play an important role. Among them is training in conditions of natural hypoxia, which, under the condition of rationally planned loads, largely determine the results achieved by athletes in competitions. This also applies in the training process of highly qualified male and female boxers. The aim of the study. Determine the dynamics of indicators of physical fitness of boxer cadets of the team of higher military educational institutions (in this example from the National Academy of Ground Forces of P. Sahaidachny) in the conditions of educational and training meetings in the highlands in the pre-competition period. Material and methods. 23 cadets - members of the men's (n=12) and women's (n=11) national boxing teams of the Academy participated in the study. The ascertainment experiment lasted for four weeks, testing the level of physical fitness took place four times. Changes in indicators of speed, power endurance, speed-power qualities, strength and coordination abilities were evaluated. The results. During the pedagogical experiment, across the stages of testing, we observed mostly positive dynamics of physical qualities in both women and men, while only at certain stages we observed statistically significant changes in some physical qualities (p
Keywords: cadets; boxers; highlands; physical fitness; physical qualities